2020
DOI: 10.1096/fasebj.2020.34.s1.00714
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Tissue Properties in Trapezius with Ultrasound Shear Wave Elastography: A Pilot Study

Abstract: Ultrasound shear wave elastography (SWE) is a relatively new technology in the field of sonography. Even more so, research into musculoskeletal applications of SWE is in its infancy. Despite challenges concerning the anisotropic nature of muscle tissue, the literature suggests that SWE is a promising medium with which to examine patterns of tissue properties in morphometrically complex muscles, like trapezius. Tissue properties can provide valuable insights into muscle function and dysfunction. In our laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Complementing the recommendations of Stiver et al (2023), the following quality criteria are suggested. (i) Measurements of muscle stiffness should be performed blinded to the group status of the participant in a strictly standardized manner.…”
Section: Discussionmentioning
confidence: 99%
“…Complementing the recommendations of Stiver et al (2023), the following quality criteria are suggested. (i) Measurements of muscle stiffness should be performed blinded to the group status of the participant in a strictly standardized manner.…”
Section: Discussionmentioning
confidence: 99%